PENGARUH STRATEGI PEMASARAN PASCA PANDEMI COVID-19 TERHADAP MINAT NASABAH MENABUNG DI BANK BSI MATARAM - Abdul Hadi Sukmana (Jurnal Perbankan Syariah, 2022)
This study aims to determine the influence of product, price, promotion and place factors on customers' interest in saving at Bank BSI Mataram. Data collection using a questionnaire. The analysis model is multiple regression analysis. The results showed that the factors of product, price, promotion, and distribution jointly affect the intention to save customers with a coefficient of determination R Square of 0.596. Product partially influences customer saving intention with a coefficient value of 0.343, price partially influences customer saving intention with a coefficient value of 0.149, promotion partially influences customer saving interest with a coefficient value of 0.208 and location partially influences customer saving intention with coefficient value of 0.200. So this research shows that marketing strategies are an integral part of the banking world to get customers interested in saving in these banks.